2020
DOI: 10.3390/ijms21145040
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms of Circulating Tumor Cells During Breast Cancer Metastasis

Abstract: Circulating tumor cells (CTCs) are cancer cells that detach from the primary site and travel in the blood stream. A higher number of CTCs increases the risk of breast cancer metastasis, and it is inversely associated with the survival rates of patients with breast cancer. Although the numbers of CTCs are generally low and the majority of CTCs die in circulation, the survival of a few CTCs can seed the development of a tumor at a secondary location. An increasing number of studies demonstrate that CTCs undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 169 publications
(246 reference statements)
0
25
0
Order By: Relevance
“…Breast tumor cells circulate in a suspended state in the blood stream during the metastatic cascade, prior to adhesion to the vascular endothelium ( Mentis et al, 2020 ). Circulating tumor cells are associated with increased risk of metastasis and lower progression-free and overall survival in breast cancer patients ( Bidard et al, 2014 ; Riebensahm et al, 2019 ; Cristofanilli et al, 2019 ; Park et al, 2020 ). We first questioned whether the three breast tumor cell clones had different sizes in suspension.…”
Section: Resultsmentioning
confidence: 99%
“…Breast tumor cells circulate in a suspended state in the blood stream during the metastatic cascade, prior to adhesion to the vascular endothelium ( Mentis et al, 2020 ). Circulating tumor cells are associated with increased risk of metastasis and lower progression-free and overall survival in breast cancer patients ( Bidard et al, 2014 ; Riebensahm et al, 2019 ; Cristofanilli et al, 2019 ; Park et al, 2020 ). We first questioned whether the three breast tumor cell clones had different sizes in suspension.…”
Section: Resultsmentioning
confidence: 99%
“…CTCs play an important role in tumor progression because of their great metastasis potential, and can circulate and disseminate within the body to seed and colonize metastasis niches. 53 For this reason, CTCs are considered as therapeutic targets for metastasis inhibition. Accumulating pieces of evidence have shown that inflammatory neutrophils are capable of targeting CTCs both in circulation and in metastasis niches due to the vascular cell adhesion molecule-1 (VCAM-1) expressed on the neutrophil membrane.…”
Section: Organic Nanomaterials In Neutrophil-based Drug Delivery Systemsmentioning
confidence: 99%
“…Besides, though CTCs are identified to express both EMT and CSCs markers 115 , they may obtain extra molecular changes during EMT and circulation. Specifically, multiple cellular mechanisms are activated and CTCs are modified to be heterogeneous with enhanced metastatic potential, bringing extra challenges for targeted drug delivery 116 , 117 . Fortunately, various novel targeting tools as well as nanovehicles have been introduced to broaden the arsenal fighting against CTCs by virtue of advanced molecular and biomedical engineering technology.…”
Section: Targeting the Circulating Tumor Cells (Seeds) Through Engineering Nanosystems: Stifling Metastasis In The Half-waymentioning
confidence: 99%